O lúdico na formação de professores da educação básica na capacitação em TIC - Lima, Andréia Lucimar Silva de (2015)
The study was conducted in primary school network in the municipalities of Joy/RS, Independence/RS and Inhacorá/RS in order to train teachers in Information and Communication Technologies, mediated by recreational activities. The research adopted was the qualitative, following the dynamics of the three pedagogical moments: questioning, organization and application of knowledge and as the goal is an exploratory research. In questioning the teachers were challenged to question about their everyday reality, in the organization were shared knowledge and was proposed joint interaction with the experiences of teachers in the application there was a systematic approach to knowledge that was built during the training. The focus of training in ICT was: the use of Prezi, ToonDoo software, and the use of learning objects, available in Educational Repositories: Teacher Portal (http://portaldoprofessor.mec.gov.br/), Web of Life (http://webeduc.mec.gov.br/portaldoprofessor/ biology/teiadavida/content/). It is noteworthy that were produced and made available tutorials of all activities of the training. The pedagogical support mediators were playing activities "Path of Life" concurrently with the "Technological Trail", "Magic Box", "Wailing Wall", "Hot Potato". Training in Information and Communication Technologies - ICT is complementary part of the outreach program PROIPE - Pedagogical Innovation Program, linked to the Department of Agricultural Education and Rural Extension of the Federal University of Santa Maria, which is characterized by a continued training action Basic Network of teachers and seeks to stimulate innovation and pedagogical actions. We conclude that the use of educational mediators recreational activities favored training in ICT. Teachers divided into four groups presented the final seminar the product of the training, the Inhacorá group showed the cartoons produced manually, the Independence presented strips made in ToonDoo, one of Joy groups presented the school Moodle and the other the strips made manually. It is considered the papers presented by teachers, that insecurity in the face of new and changes that come from these new techniques interfered so that the changes expected in their teaching practices did not occur to full strength during training in ICT.